Answer:
p - 2q and p - 3q
Step-by-step explanation:
A Series is given to us and we need to find the next two terms of the series . The given series to us is ,
[tex]\rm\implies Series = p+q , p , p - q [/tex]
Note that when we subtract the consecutive terms we get the common difference as "-q" .
[tex]\rm\implies Common\ Difference = p - (p + q )= p - p - q =\boxed{\rm q}[/tex]
Therefore the series is Arithmetic Series .
Arithmetic Series:- The series in which a common number is added to obtain the next term of series .
And here the Common difference is -q .
Fourth term :-
[tex]\rm\implies 4th \ term = p - q - q = \boxed{\blue{\rm p - 2q}}[/tex]
Fifth term :-
[tex]\rm\implies 4th \ term = p - 2q - q = \boxed{\blue{\rm p - 3q}}[/tex]
Therefore the next two terms are ( p - 2q) and ( p - 3q ) .